Performance of the VITEK MS matrix-assisted laser desorption ionization-time of flight mass spectrometry system for rapid bacterial identification in two diagnostic centres in China. Issue 1 (January 2015) - Luo, Yanping; Siu, Gilman K. H.; Yeung, Amy S. F.; Chen, Jonathan H. K.; Ho, Pak Leung; Leung, K. W.; Tsang, Jacqueline L. Y.; Cheng, Vincent C. C.; Guo, Ling; Yang, Jiyong; Ye, Liyan; Yam, Wing-Cheong
Abstract : Matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) MS systems was not officially launched for diagnostic use in clinical microbiology laboratories in China until 2012. Here, we report the findings from the first large-scale evaluation study of VITEK MS for routine bacterial identification in two major diagnostic centres in Beijing and Hong Kong. A total of 2266 unique isolates representing 56 genera and 127 species were analysed, and results were compared to those obtained by VITEK 2. Any discrepancies were resolved by 16S rRNA sequencing. Overall, VITEK MS provided correct identification for 2246 (99.1 %) isolates, including 2193 (96.8 %) with correct species-level identifications and 53 (2.3 %) matched at the genus level only. VITEK MS surpassed VITEK 2 consistently in species-level identification of important pathogens, including non- Enterobacteriaceae Gram-negative bacilli (94.7 versus 92 %), staphylococci (99.7 versus 92.4 %), streptococci (92.6 versus 79.4 %), enterococci (98.8 versus 92.6 %) and Clostridium spp. (97.3 versus 55.5 %). The findings demonstrated that VITEK MS is highly accurate and reliable for routine bacterial identification in clinical settings in China. Abbreviations: IVD, in vitro diagnostic; MALDI-TOF, matrix-assisted laser desorption ionization-time of flight.